INFLUENTIAL FACTORS IN DESIGN AND IMPLEMENTATION OF VIRTUAL REALITY TECHNOLOGY - Zel, Serap; Kongar, Elif (MATTER: International Journal of Science and Technology, 2020)
Virtual Reality (VR) is a computer-generated environment that creates a simulated experience for users. VR technology is used as an effective training tool, especially for teaching potentially dangerous and/or difficult-to-create scenarios in real-life. Despite the vast literature that shows the positive impact of VR training on the learners’ performance and experience, studies that investigate the criteria for the selection of appropriate VR technology are quite limited. This paper proposes key decision criteria in selecting and investing in the right VR technology to create the best possible learning outcome based on the feedback from VR developers and engineers in the US. Ease of installation and creating an immersive user experience are identified as the most influential factors affecting the successful implementation of VR technology. We envision that this study will help companies that plan to invest in VR technologies better understand the critical factors affecting the successful design and implementation of the technology and hence will aid in decision making.